RELATIONSHIP BEHAVIOR OF STUDENTS ON THE MAINTENANCE OF ORAL HEALTH TOWARDS FIGURES OF CARIES IN CLASS VII MTSN 2 PONTIANAK CITY - Asny Asny; Endah Aryati (Jurnal Riset Kesehatan, 2020)
Behavior is one of the factors that affect oral health can affect the dental health status of individuals or society. The behavior may also influence the risk of caries. The purpose of this research is to know there is a Student Behavior Relationships On Dental and Oral Health Care Score Against Caries In Seventh Grade Students MTSN 2 Pontianak.Type of research is descriptive correlation method with cross sectional study design. Sample namely Seventh Grade Students MTSN 2 Pontianak totaling 83 sampling purposive sampling technique. Data was analyzed using univariate and bivariate analysis of the research data was analyzed statistically by Chi-Square Test. Results of student behavior research on dental and oral health care to the DMFT figures show knowledge (p = 0.000), physics (p = 0.000), Action (p = 0.000). It can be concluded that there is a relationship of student behavior on the maintenance of oral health to the number of caries in class VII MTSN 2 Pontianak.